Advances on Broad-Band Wireless Computing, Communication and Applications Proceedings of the 11th International Conference On Broad-Band Wireless Computing, Communication and Applications (BWCCA-2016) November 5-7, 2016, Korea - Barolli, Leonard; Xhafa, Fatos; Yim, Kangbin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The success of all-IP networking and wireless technology has changed the ways of living the people around the world. The progress of electronic integration and wireless communications is going to pave the way to offer people the access to the wireless networks on the fly, based on which all electronic devices will be able to exchange the information with each other in ubiquitous way whenever necessary. The aim of the volume is to provide latest research findings, innovative research results, methods and development techniques from both theoretical and practical perspectives related to the emerging areas of broadband and wireless computing. This proceedings volume presents the results of the 11th International Conference on Broad-Band Wireless Computing, Communication And Applications (BWCCA-2016), held November 5-7, 2016, at Soonchunhyang University, Asan, Korea. .
From the Content -- C++ Memory Check Tool Based on Dynamic Binary Instrumentation Platform -- A Program Behavior Recognition Algorithm Based on Assembly Instruction Sequence Similarity -- Energy-aware Migration of Virtual Machines in a Cluster -- An Energy-efficient Migration Model of Processes with Virtual Machines in a Server Cluster.
Keywords: Telecommunication; Communications Engineering, Networks